MODEL ENTREPRENURSE: TINJAUAN INTEGRATIF - Grace Fresania Kaparang; Anthony Stafford Pangemanan; Nova Lina Langingi (Fakultas Ilmu Keperawatan Universitas Klabat, 2022)
Abstract The unemployment rate of nurses is increasing and there are still many who adhere to the traditional perspective of the nursing profession as employees. This global competitive era, as well as this pandemic, requires out-of-the-box nurses who dare to open nursing practices as entrepreneurs in overcoming the rising of unemployment. The study attempted to investigate entrepreneurial nurse model with Whittemore and Knafl's integrative review design, analyzing the quality of the articles with the Alberta Heritage Foundation's QualSyst tool. The search strategy is with the keywords